Feasibility and effectiveness of a smartphone access program for promoting engagement in care among perinatal people with substance use disorders: a pilot study - Goodman, D. J.; Lamadriz, L.; Stokes, K.; Adams, M.; Martell, H.; Robie, K.; Morgan, A.; Saunders, E. C. (Frontiers in Health Services, 2025)
IntroductionPregnant and postpartum people with substance use disorders (SUD) experience high rates of morbidity and mortality, especially postpartum. For this vulnerable group, lack of access to a phone contributes to poor engagement in perinatal care. This paper describes initial work evaluating the implementation of a free smartphone program for rural pregnant patients with SUD and its effectiveness for improving participation in care.MethodsThis retrospective type I hybrid-effectiveness cohort study evaluated program effectiveness, acceptability, and feasibility of implementation in obstetric practice. Semi-structured interviews with patients, providers and obstetric staff (n = 8) explored implementation success. Data on phone utilization, engagement in care and outcomes were abstracted from electronic health records and compared among three cohorts (Cohort 1: patients with SUD who received phones; Cohort 2: patients with SUD not receiving phones; Cohort 3: Patients without SUD). Kruskal–Wallis and chi-squared/Fisher's Exact tests were utilized for comparisons.ResultsProviders, staff, and patients universally found the smartphone access program useful, perceiving that it improved patient engagement in digital and in-clinic care. From 2021 to 2024, 44 patients with SUD participated in the smartphone program for an average of 162 days. Cohort 1 entered prenatal care later, attended fewer prenatal visits, and were more likely to have psychiatric comorbidity than Cohorts 2 and 3. After receiving a smartphone, there were no differences in postpartum visits between cohorts, and higher rates of behavioral health and recovery support for Cohort 1.DiscussionIn a rural obstetric clinic, implementing a free smartphone program for perinatal patients with SUD was feasible and acceptable. Though there was no difference in prenatal care utilization, patients who received a smartphone engaged in robust postpartum care and behavioral healthcare utilization. Addressing digital disparities is an essential component of health equity.